A Novel Concept of a Phased-Array HIFU Transducer Optimized for MR-Guided Hepatic Ablation: Embodiment and First In-Vivo Studies - Lorton, Orane; Guillemin, Pauline C.; M’Rad, Yacine; Peloso, Andrea; Boudabbous, Sana; Charbonnier, Caecilia; Holman, Ryan; Crowe, Lindsey A.; Gui, Laura; Poletti, Pierre-Alexandre; Ricoeur, Alexis; Terraz, Sylvain; et al. (Frontiers in Oncology, 2022)
Purpose: High intensity focused ultrasound (HIFU) is challenging in the liver due to the respiratory motion and risks of near/far field burns, particularly on the ribs. We implemented a novel design of HIFU phased array transducer, dedicated to transcostal hepatic thermo-ablation. Due to its large acoustic window and strong focusing, the transducer should perform safely for this application. Material and methods: The new HIFU transducer is composed of 256 elements distributed on 5 concentric segments, of specific radius either 100 mm, 111 mm or 125 mm. It has been optimally shaped to fit the abdominal wall. The shape and size of the acoustic elements were optimized for the largest emitting surface and the lowest symmetry. Calibration tests have been conducted on tissue mimicking gels under 3T magnetic resonance (MR) guidance. In vivo MR-guided HIFU treatment was conducted in two pigs, aiming to create a thermal ablation deep in the liver without significant side effects. Imaging follow-up was performed at D0 and D7. Sacrifice and post-mortem macroscopic examination occurred at D7, with the ablated tissue being fixed for pathology. Results: The device showed -3dB focusing capacities in a volume of 27 x 46 x 50 mm3 as compared to the numerical simulation volume of 18 x 48 x 60 mm3. The shape of the focal area was in mm-range agreement with the numerical simulations. No interference was detected between the HIFU sonication and the MR acquisition. In vivo, the temperature elevation in perivascular liver parenchyma reached 28°C above physiological temperature, within one breath-hold. The lesion was visible on Gd contrast-enhanced MRI sequences and the post-mortem examination. The non-perfused volume was found in pig#1 and pig#2 of 8/11, 6/8, 7/7 mm along LR, AP and HF directions, respectively. No rib burns or other near field side effects were visually observed on post-mortem gross examination. High resolution contrast-enhanced 3D MRI indicated a minor lesion on the sternum. Conclusion: The performance of this new HIFU transducer has been demonstrated in vitro and in vivo. The transducer meets the requirements to perform thermal lesions in deep tissues, without a need for rib sparing means.